(untitled) (Caring: Indonesian Journal of Nursing Science, 2023)
The COVID-19 pandemic has increased workloads and psychologically affected the nurses due to a long time of exposure to the virus, and causes a decrease in energy, leading to stress and fatigue. This study aims to analyze the factors associated with fatigue and stress experienced by nurses in the COVID-19 isolation room in Indonesia.Â This study involved 50 nurses who worked in the hospital’s COVID-19 isolation room. The instrument used consists of three parts, namely the demographic data, a Fatigue Scale-14 questionnaire, and a Perceived Stress Scale-10. The results of the validity and reliability tests carried out on both instruments were declared valid and reliable. The data were collected by providing questionnaire link in form of a google form link through WhatsApp to each research sample. Subsequently, the collected data were analyzed using cross-tabulation analysis and chi-square test.Â Results showed that the majority of respondents were aged 31-40 years and most were female (35%). A total of 64% experienced moderate fatigue and 82% of nurses were in the moderate stress category. Based on the fatigue data tabulation analysis, there is no relationship between demographic data variables and fatigue. However, there is a relationship between work duration and stress variables as well as fatigue and stress experienced by nurses.Â These results showed that the stress and fatigue experienced by COVID-19 nurses are related to the nursesâ€™s certain characteristics that have the potential to worsen mental health conditions.Â It Is recommended to explore more related to fatique factors in the future with specific nursing interventions.